(Uranium + thorium)/helium dating of apatite: experience with samples from different geochemical environments - Lippolt, Hans J.; Leitz, Markus; Wernicke, Rolf Stephan; Hagedorn, Birgit (Chemical geology, 1994)
U-He dating, which during its history has been very problematic, might find special application in the field of hydrothermal mineralizations where other methods generally fail. The mineral apatite is a potential candidate for this method. In order to shed light on various aspects of apatite dating by the (U + Th)/He method, two samples each from different geochemical environments (plutonic, pneumatolytic and hydrothermal) were probed. Isotope dilution techniques were used for concentration analyses from which 4He model dates, also called “helium indices” after N.B. Keevil, were calculated. 4He diffusion measurements were carried out for comparison of the 4He retentivities between the samples. Comparisons of the apatite He indices with plausible reference ages of the sampling locations in combination with results obtained from diffusion experiments show that the (U + Th)/He dating method applied to apatite yields an age of cooling rather than an emplacement age. The calculated closure temperatures are similar to those obtained by the fission-track method (∼ 100°C). Our results suggest that the high-temperature apatites (plutonic and pneumatolytic) may be more suitable for He dating than hydrothermal apatite. Important criteria for the dating of apatite by (U + Th)/He are the presence of moderate radionuclide concentrations (tens of ppm) and a minimum abundance of inclusions.